Can the Horse be Modern? Review of Kristen Guest and Monica Mattfeld, eds. Equestrian Cultures: Horses, Human Society, and the Discourse of Modernity - Renton, Kathryn (Humanimalia, 2020)
Kristen Guest and Monica Mattfeld, eds. Equestrian Cultures: Horses, Human Society, and the Discourse of Modernity. Chicago: University of Chicago Press, 2019. 276 pp. 90.00 (hb), 30.00 (pb).